Jessica Forney: capstone - Forney, Jessica, artist (Colorado State University. Libraries, 2019)
The artist's statement: I work in a variety of different media and on a vast variety of projects. I typically work in illustration and typography, UX/UI design, and electronic media (photography, info-graphics, and video primarily). I view graphic design as a visual communication media and my work typically takes a concept and uses illustration and typography to showcase key elements of that concept to convey a message. My work as a whole does not have a universal theme, aside from the fact that I do try experimenting with different graphic design outputs (posters, logos, magazine spreads, etc.) and variety of concepts (CSU, article-based content, real-world events, novels, femininity, etc.) in order to get a jack-of-all-trades experience.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design; illustration; typography; poster